A model for detecting fake Negative Acknowledgements (NACK) in named Data Network (NDN) using Blockchain Technology - Saha, Ritwick; Shiva, Tahsina; Akter Tayeeba, Kazi Sharmin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.